Multi-omics analysis reveals the impact of influenza a virus host adaptation on immune signatures in pig tracheal tissue - Laybourn, Helena Aagaard; Hellemann Polhaus, Chrysillis; Kristensen, Charlotte; Lyngfeldt Henriksen, Betina; Zhang, Yaolei; Brogaard, Louise; Larsen, Cathrine Agnete; Trebbien, Ramona; Larsen, Lars Erik; Kalogeropoulos, Konstantinos; auf dem Keller, Ulrich; Skovgaard, Kerstin (Frontiers in Immunology, 2024)
Influenza A virus (IAV) infection is a global respiratory disease, which annually leads to 3-5 million cases of severe illness, resulting in 290,000-650,000 deaths. Additionally, during the past century, four global IAV pandemics have claimed millions of human lives. The epithelial lining of the trachea plays a vital role during IAV infection, both as point of viral entry and replication as well as in the antiviral immune response. Tracheal tissue is generally inaccessible from human patients, which makes animal models crucial for the study of the tracheal host immune response. In this study, pigs were inoculated with swine-or human-adapted H1N1 IAV to gain insight into how host adaptation of IAV shapes the innate immune response during infection. In-depth multiomics analysis (global proteomics and RNA sequencing) of the host response in upper and lower tracheal tissue was conducted, and results were validated by microfluidic qPCR. Additionally, a subset of samples was selected for histopathological examination. A classical innate antiviral immune response was induced in both upper and lower trachea after infection with either swineor human-adapted IAV with upregulation of genes and higher abundance of proteins associated with viral infection and recognition, accompanied by a significant induction of interferon stimulated genes with corresponding higher proteins concentrations. Infection with the swineadapted virus induced a much stronger immune response compared to infection with a humanadapted IAV strain in the lower trachea, which could be a consequence of a higher viral load and a higher degree of inflammation. Central components of the JAK-STAT pathway, apoptosis, pyrimidine metabolism, and the cytoskeleton were significantly altered depending on infection with swine-or human-adapted virus and might be relevant mechanisms in relation to antiviral immunity against putative zoonotic IAV. Based on our findings, we hypothesize that during host adaptation, IAV evolve to modulate important host cell elements to favor viral infectivity and replication.